1997
DOI: 10.1016/s0029-7844(97)00440-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo-controlled evaluation of terbutaline for external cephalic version

Abstract: Terbutaline (0.25 mg) administered subcutaneously before an attempted version in women at term with noncephalic presentations significantly increased the initial success rate of version and the rate of cephalic presentations in labor while decreasing the rate of cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 14 publications
2
15
0
9
Order By: Relevance
“…Fifteen reports were excluded for not reporting an AFI in their results despite using oligohydramnios as a study exclusion criterion [8,[27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Seven trials reported AFI values but did not correlate the values to the success of the ECV [41][42][43][44][45][46][47]. Four reports mentioned that results with 'normal' fluid were better than those with oligohydramnios or 'decreased' fluid but did not report specific AFI values [5,9,15,48].…”
Section: Sources and Study Selectionmentioning
confidence: 99%
“…Fifteen reports were excluded for not reporting an AFI in their results despite using oligohydramnios as a study exclusion criterion [8,[27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Seven trials reported AFI values but did not correlate the values to the success of the ECV [41][42][43][44][45][46][47]. Four reports mentioned that results with 'normal' fluid were better than those with oligohydramnios or 'decreased' fluid but did not report specific AFI values [5,9,15,48].…”
Section: Sources and Study Selectionmentioning
confidence: 99%
“…Looking at the studies in our analysis a value of 3.7% was calculated. Almost all cases (16/18), however, are derived from one study, in which the author already addresses his concerns about the accuracy of data collection (20). Leaving this study out would result in an incidence of only 0.5%.…”
Section: Bleedingmentioning
confidence: 99%
“…It has now been clearly shown that an attempt at external cephalic version at term can reduce the frequency of breech presentation and the rate of caesarean sections performed for this indication 3 . Several randomised placebo‐controlled trials have shown that the success rate of external version is higher when performed with beta‐mimetics 4–7 . External version under epidural anaesthesia has been proposed to improve the success rate, since it would reduce the pain and anxiety associated with the procedure as well as contribute to reducing abdominal and perhaps uterine muscle tone 8 .…”
Section: Introductionmentioning
confidence: 99%